Edukasi Pengaruh pola pengasuhan Edukasi pengaruh pola pengasuhan yang baik terhadap masa depan bangsa pada masyarakat desa karangnongko - Firyal, Khazana (Maliki Interdisciplinary Journal, 2025)
Parenting style has a great influence on the growth of character in children. Improper parenting can affect the development of children's personality which will later have an impact on their attitudes and behaviors when in the community. Because it is necessary to educate the public about good parenting to produce a generation of the nation that will later contribute to the future of the nation, especially people who are located in the mountains and have a fairly high rate of early marriage.The purpose of this service is to increase the knowledge and understanding of the community in Karangnongko Village about the importance of good parenting which will have an impact on the growth of children's character as the nation's successor. The type of research used in this study is qualitative with a library research approach. From the educational activities that have been carried out, it has increased the importance of good parenting, especially democratic parenting, love language and the